Analysis of a closed-loop water-cooled refrigeration system in the food retail industry: A UK case study. (1st May 2019) - Efstratiadi, Marily; Acha, Salvador; Shah, Nilay; Markides, Christos N.
Abstract: Refrigeration in supermarkets accounts between 30% and 60% of total electricity demand in UK stores. The aim of this study is to conduct a pre-feasibility analysis of whether the use of a water-cooled configuration rejecting heat to the soil can improve the overall cooling performance of commercial refrigeration systems against air-cooled designs. In this work, a model simulating the operation of an existing refrigeration system is presented and validated against field data measurements taken from a supermarket. The examined system is used as a baseline and then modified to evaluate the impact of installing a water-cooled gas cooler. Results indicate that the use of water-cooled gas coolers has the potential to reduce electrical consumption of refrigeration systems by up to a factor of 5 when external temperatures are high. Overall, annual operation indicates the water-cooled alternative uses 3% less electricity than the air-cooled approach. A hybrid system is also considered consisting of coupled air-cooled and water-cooled units operating in parallel, for which an energy reduction of 6% is obtained compared against the baseline system. An economic evaluation of these systems shows promising results with a payback period of about 5 years for systems installed in new stores, although retrofits are costlier. Highlights: A modelling framework to compare different refrigeration systems is presented. Water-cooled systems outperformed the air-cooled systems by 3% in the UK. Water-cooled solutions can reduce energy use but have higher initial costs. External temperature conditions impact the operation of a water-cooled condensers. A hybrid approach maximises energy savings by 6% against air-cooled systems.